Do Oligopolists Earn "Noncompetitive" Rates of Return? - Alberts, William W. (American Economic Review, 1984)
High, in effect, is defined in this proposition in either of two ways. Most commonly, it has been taken to mean: high enough to warrant remedial intervention of some sort by the state.4 Recently, however, a growing minority of economists has urged that it be taken to mean instead: high enough to warrant intervention, provided the state can show that rates of return in excess of R1 reflect collusive behavior by the leading firms and not cost advantages which these firms have over their leading rivals.' Both meanings in turn reflect a third: high enough to imply a typical market price closer to PM in Figure lb than to Pc' where PM is the price that would prevail if the leading firms maximized collective, current-period profits and Pc is the price that would prevail if collective, current-period profits approximated zero.6 Proposition 1 rests on a large body of empirical work. Proposition 2, however, does not; nor does it rest on any theoretical analysis. Industrial economists simply have intuited that there is a correspondence between the R1R2 segment in Figure la and the PMP* segment in Figure lb. Are there substantive grounds for the intuition? I argue that there are not. The rates of return that lie along the R1R2 segment are competitive,